Transition of Countries to Currency and Trade Sustainable International Cooperation on the BRICS Platform - Evgeniy Bryndin (Journal of World Economy, 2023)
The transition to monetary and trade sustainable cooperation within the BRICS can be carried out on the basis of the energy economic equivalent of the national currencies of sovereign states. The International Monetary Index will link the existing commodity masses of states with national currencies. The creation of two-circuit national monetary and financial systems will create conditions for the evolutionary transition of budget formation. Double-circuit monetary and financial systems will bind national currencies to energy economic equivalents and goods. An interim measure of the national currency due to the energy economic equivalent and a group of goods with both commodity and monetary properties creates their currency value. This makes it possible to estimate their value in the energy economic equivalent. The energy economic equivalent can become a meter of the intrinsic value of any payment means. The economic reserve base, expanded at the expense of groups of goods, makes it possible to create a stable basis for strengthening national currencies in the system of domestic, regional and international settlements, maintaining their stability. It is possible to connect the financial and real sectors of the international economy of sovereign states through the BRICS investment international bank. This will allow the generation of long and cheap financial resources by issuing securities and digital financial assets secured by a group of goods with foreign exchange value. National currencies will become full-fledged, tied to the amount of those resources that are in the provision of the BRICS investment international bank.